Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Dalam Penentuan Titik Batas Desa wilayah Kabupaten Barito SelatanThe Effect of Work Discipline on Employee Performance in Determining the Village Boundary Points in the South Barito Regency - Lisawanto Lisawanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This research was conducted in order to describe the performance of the employees of the Regional Secretariat of the South Barito Regency government officials, to the performance of employees in the government division in carrying out their duties and coordination in determining and affirming village boundaries in the South Barito district. This study aims to determine the effect of work discipline on employee performance in the government division of the South Barito regency. The theory used in this research is Work Discipline according to Bejo Siswanto (2019: 333) and employee performance theory according to Ags Dwiyanto (2017: 47). This research uses descriptive quantitative method with data collection techniques using observation, interviews, documentation, and questionnaires. This researcher has two variables, namely the independent variable (x) Work Discipline and the dependent variable (y) the performance of the government employees of the Regional Secretariat of the South Barito Regency. The data analysis tool used is Simple Linear Regression using SPSS Version 25. The hypothesis in this study is. It is suspected that there is an influence of work discipline on the employee performance of the Regional Secretariat of Barito Regency. The results obtained in the calculation of simple linear regression are Y = 11.470 + 0.745 X where the value (a) is 11.470 and the coefficient value (b) is 0.745. Then the tcount is obtained from the above test that tcount> ttable (9.197> 2.021) then Ho is rejected and Ha is accepted, meaning that there is a significant influence between Work Discipline on Employee Performance at the Regional Secretariat of South Barito Regency.